SOME EPIZOOTOLOGICAL ASPECTS OF DISTRIBUTION OF CATTLE IXODIDOSIS IN DIFFERENT LANDSCAPE ZONES OF DAGESTAN - M. V. Arisov; G. M. Magomedshapiev (Российский паразитологический журнал, 2016)
Distribution and seasonal activity of ixodid ticks in various landscape zones of Dagestan is studied. During investigation of ixodid fauna in cattle we took into account the intensity of infection and index of abundance. After examination of50 animals in plain areas in 2012, we determined that 100 % of animals were infected with ixodid ticks, index of abundance was 369,0 expl. In 2013 we investigated 50 animals in the piedmont of Dagestan, ixodid tickswere detected in100 % of tested animals, index of abundance was 269,5 expl. In mountain areas of Dagestan all animals were also infected, index of abundance was 157, 4 expl.